2009
DOI: 10.1037/a0016550
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial development from college through midlife: A 34-year sequential study.

Abstract: Two cohorts of alumni, leading-edge and trailing-edge baby boomers, first tested in their college years, were followed to ages 43 (N = 136) and 54 (N = 182) on a measure of Erikson's theory of psychosocial development. Hierarchical linear modeling was used to model the trajectory of growth for each psychosocial issue across middle adulthood. As predicted, the early psychosocial issues (trust, autonomy, and initiative) showed patterns of slow and steady increases in favorable resolution, as did the midlife issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 38 publications
9
84
1
2
Order By: Relevance
“…Because the so-called "midlife crisis" is essentially a revisiting of identity issues in the 40s and 50s (Freund & Ritter, 2009), resolving Ihese identity issues in a coherent and positive way appears to facilitate satisfaction with work, family, and life in general. The present results support Erikson's (1950) contention that identity and intimacy remain important throughout the life span (see also Whitboume et al, 2009). Although identity is most often studied in adolescents and young adults, it clearly remains important for psychosocial adjustment well into adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…Because the so-called "midlife crisis" is essentially a revisiting of identity issues in the 40s and 50s (Freund & Ritter, 2009), resolving Ihese identity issues in a coherent and positive way appears to facilitate satisfaction with work, family, and life in general. The present results support Erikson's (1950) contention that identity and intimacy remain important throughout the life span (see also Whitboume et al, 2009). Although identity is most often studied in adolescents and young adults, it clearly remains important for psychosocial adjustment well into adulthood.…”
Section: Discussionsupporting
confidence: 93%
“…However, most cross-sectional studies did not find differences according to age (Hannah et al, 1996;Ryff & Heincke, 1983;Webster, 2003;see however, Domino & Affonso, 1990). The longitudinal Rochester study also did not find evidence of an increase with age (Sneed, Whitbourne & Culang, 2006;Whitbourne, Sneed, & Sayer, 2009). Hence, ego integrity and despair are more a matter of the resolution of previous dilemmas of human development than of chronological age.…”
mentioning
confidence: 87%
“…Given the sufficient time points in our data, a The significant negative effect of cubic growth (β = -0.012475, SE = 0.000674, p < 0.01) suggested that the acceleration rate of change in the CPYD12 indicator scores slowed over time (i.e., a slower decrease after the end of the program) ( Appendix 4). Generally, if the higher order polynomial trends fit the data better than the linear trend, interpretation of the data would focus on the higher order polynominal trends [19][20][21]. For example, Taylor et al [22] found that the beneficial effects of prevention program with a higher order function of growth in drug use.…”
Section: Step 4: Unconditional Cubic Growth Model (Model 4)mentioning
confidence: 99%